LOAD BALANCING 2 JALUR INTERNET MENGGUNAKAN MIKROTIK ROUND ROBIN - Leman, Dedi (Riau Journal Of Computer Science, 2019)
Many of us have encountered Internet use, especially in internet cafes, offices, schools and campuses using more than one connection in subscribing to the Internet, whether it's different ISPs (Internet Service Providers) or the same ISP. In accessing the Web there are 2 types, namely with Authentication and without Authentication. At this writing the author uses 2 (two) Asymmetric Digital Subscriber Line or ADSL connections up to 3 Mbps from an Internet Service Provider (ISP). Cluster architecture that is implemented as a high-performance server is one of the effective and efficient solutions to overcome this problem. This cluster architecture can be built using the concept of network load balancing with high-availability that allows the processing of data to be distributed in a distributed manner to several computers. In Linux virtual servers there are scheduling algorithms that can affect LVS work systems, one of which is the round robin algorithm. By using a round robin algorithm, the workload will be shared equally across all servers. Round robin algorithm testing is done by using parameters comparing the number of users and response times, so that the response time is stable between 31 ms to 76.3 ms with the number of users between 10,000 and 50000 in load balancing implementation using the round robin algorithm